The Development of a Portable Gas Leak Detection System Using IoT - Mohamad Asri, Nur Aniqah Syamimi (IRC, 2019)
There are high-risk issues involved in industries which use hazardous gases in large quantities for their various processes. People may not identify or monitor the leakage of these gases on a regular basis before it goes out of hand. There is a need for sensors to continuously monitor the leakages and alert the users on the possible hazard. This project gives the solution to reduce the risk factors in isolated areas having large gas installations by detecting and displaying the leakages continuously. Leakage of gas can occur at multiple points in the same installation. Hence, multiple sensors are implanted as close as possible to the potential leak site and able to detect the leakage and transmit the signals to the base station located far away. Using microcontroller, multiple sensor values are received and processed. The processed data is encoded in Wireless Module and transmitted to the base via the Internet of Things connection where another microcontroller decodes it and shows the respective sensor status. The system also gives an audio and visual warning when leakages are detected and as the time taken to detect is very low due to high-speed processing, the leakage situations are brought under control with minimal or no damage. This project gives an economical and efficient method to reduce leakage risk by using latest IoT technologies and monitoring anywhere on the web.